Target Waktu Pelaporan Manajemen Tahunan dalam Penerapan Good Corporate Governance (GCG) di Perum Perumnas - Putra, Didi Hasan; Pramesti, Adelia Putri (JURNAL MAHASISWA BINA INSANI, 2023)
The implementation of Good Corporate Governance (GCG) is the foundation for creating a company that develops sustainably. To support the implementation of GCG, Perum Perumnas, which is one of the state-owned enterprises (BUMN), makes the GCG Implementation Score an indicator in assessing company performance with KPIs (Key Performance Indicators). In implementing GCG, several Management Reports must be submitted by the company both to shareholders and stakeholders promptly. In reality, the target time for submitting Management Reports is sometimes not always following predetermined time standards. For this reason, this study aims to optimize the monitoring of Annual Management Reports so that they can be delivered promptly and can achive work targets in Perum Perumnas. This research is in the form of research results from observations and interviews with the person in charge of the Management Report. Through monitoring activities, it is expected to increase transparency both from the units responsible for their respective fields and from the Corporate Secretary and his staff to be able to monitor the delivery time in real-time. In addition, the flowchart applied is expected to be a guide both in the process of creating and submitting Management Reports.